Pendidikan Tentang Pencegahan dan Manajemen Hidup Sehat sebagai Antisipasi Penularan Covid 19 di Wilayah Kerja Puskesmas Anak Air Kota Padang - Nike Sari Oktavia; Faridah BD; Eravianti (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The government has made various efforts to reduce the spread of Covid 19, but there are still many people who do not comply with health protocols. Low public knowledge and misinformation are the causes, and there is even a perception in the community that Covid 19 does not exist and is only an issue to scare the public. The purpose of this community service activity is to increase public knowledge by providing an explanation of Covid 19 and efforts that can be made to reduce its spread. It is hoped that increased knowledge can increase understanding so that people are willing and obedient to do 3M and want to be vaccinated. The method of community service activities is by distributing questionnaires, after being filled in completely, collected before and after counselling activities on Covid 19 using PPT and LCD media. Of the 67 respondents, knowledge about Covid 19 before counselling was 23.9% less, 22.4% sufficient, and only 53.7% good. After counselling knowledge became 14.9% less, 19.4% sufficient, and 65.7% good. Counselling or information can increase public knowledge about Covid 19. It is recommended to academics, health practitioners, and stakeholders to further improve the provision of information about Covid 19 to the public. The use of informative and educational videos can be one solution.